Improving Students' Speaking Skill throungh Communicative Activities In Small Group Discussion at the Third Semester Class A Of the English Study Program of FKIP UNRI - Hadriana, Hadriana (English Education Department, Universitas Islam Indonesia, 2008)
This research was intended to know whether communicative activities in small group discussions can improve the students' speaking skill at the third semester Class A of the English Study Program of FKIP UNRI. The researcher was helped by a collaborator and used observation sheets and field notes as the instruments of the research. Besides, she also used speaking test to see the improvement of students' speaking skill on each cycle. The research started on September 23,2008 and ended on January 9, 2009. At the beginning of cycle 1the average score of the students' speaking skill was 48.3. At the end of cycle 1, it improved to 55.7, at the end of cycle 2 it improved to 62.6, and at the end ofcycle3itimproved to 73.4.The factors of communicative activities in small group discussions that influence the students' speaking skill are: (1) Clear objectives; (2) problem solving activities; (3) a good classroom atmosphere; (4) natural learning process (5) uncontrolled materials; (6) indirect corrections; and (7) interaction with partners or group members. Based on the finding, it was concluded that communicative activities of small group discussions can improve students' speaking skill at the third semester Class A of the English Study Program of FKIP UNRI